2021
DOI: 10.3390/ph14010038
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of LDD-2633 as a Novel RET Kinase Inhibitor with Anti-Tumor Effects in Thyroid Cancer

Abstract: Rearranged during transfection (RET), a receptor tyrosine kinase, is activated by glial cell line-derived neurotrophic factor family ligands. Chromosomal rearrangement or point mutations in RET are observed in patients with papillary thyroid and medullary thyroid carcinomas. Oncogenic alteration of RET results in constitutive activation of RET activity. Therefore, inhibiting RET activity has become a target in thyroid cancer therapy. Here, the anti-tumor activity of a novel RET inhibitor was characterized in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Indirubin activity may be further enhanced by chemical modifications, and several new derivatives were described that showed antitumor activities in in vitro and in vivo tumor models, such as for non-small cell lung cancer, glioblastoma, breast, bladder, thyroid, hepatocellular and colorectal cancer [41][42][43][44][45][46]. We have previously reported a series of new indirubin derivatives based on N-glycosylated 3-alkylideneoxindoles containing halogen substituents [30,32].…”
Section: Discussionmentioning
confidence: 99%
“…Indirubin activity may be further enhanced by chemical modifications, and several new derivatives were described that showed antitumor activities in in vitro and in vivo tumor models, such as for non-small cell lung cancer, glioblastoma, breast, bladder, thyroid, hepatocellular and colorectal cancer [41][42][43][44][45][46]. We have previously reported a series of new indirubin derivatives based on N-glycosylated 3-alkylideneoxindoles containing halogen substituents [30,32].…”
Section: Discussionmentioning
confidence: 99%
“…Jeong et al [108][109][110] further demonstrated that these piperazinium hydrochloride derivatives of indirubin-3 -oxime were potent inhibitors of FLT3 kinase and MV4-11 cells, with compounds 53 and 54 exhibiting the highest potency. Docking studies suggested that compound 53 bound tightly to the ATP binding pocket in FLT3, surrounded by residues Leu616, Leu818, Cys828, and Tyr693, and forming approximately five hydrogen bonds with these residues [108,109].…”
Section: Classes Of Anticancer Oximesmentioning
confidence: 99%
“…Jeong et al [108][109][110] further demonstrated that these piperazinium hydrochloride derivatives of indirubin-3 -oxime were potent inhibitors of FLT3 kinase and MV4-11 cells, with compounds 53 and 54 exhibiting the highest potency. Docking studies suggested that compound 53 bound tightly to the ATP binding pocket in FLT3, surrounded by residues Leu616, Leu818, Cys828, and Tyr693, and forming approximately five hydrogen bonds with these residues [108,109]. While the indirubin core formed two significant hydrogen bonds with the backbone Cys694 residue, the tertiary amine of the piperazine moiety formed a hydrogen bond with Asn816, and the terminal amino group established two hydrogen bonds with both Asn816 and Asp829 [108,109].…”
Section: Classes Of Anticancer Oximesmentioning
confidence: 99%
See 2 more Smart Citations